Role of extended lymphadenectomy in the treatment of pancreatic head adenocarcinoma: review and meta‐analysis. Issue 10 (28th October 2013) - Svoronos, Christos; Tsoulfas, Georgios; Katsourakis, Anastasios; Noussios, Georgios; Chatzitheoklitos, Euthymmios; Marakis, N. Georgios
Abstract Background Extended lymph node dissection has been established as the method of choice in the treatment of many digestive malignancies, but its role in the treatment of adenocarcinoma of the pancreas remains controversial. Objectives The goal is to evaluate the role of extended lymph node dissection in pancreatic head adenocarcinoma and to review how it affects survival, morbidity, mortality and post‐operative quality of life. Methods A computerized search was made of the Medline database from January 1973 to October 2012. Fifteen non‐duplicated studies, four randomized and 11 non‐randomized, comparing extended radical pancreaticoduodenectomy (ERP) and standard pancreaticoduodenectomy were reviewed. Five‐year overall survivals were compared using the MetaXL software in eight of these studies, where the necessary data were available. Results The 5‐year survival after ERP ranged from 6 to 33.4% and the local recurrence incidence from 8 to 36.1%, while the incidence of severe diarrhoea, one of the main complications, ranged from 10.8 to 42.4%. Meta‐analysis showed that there was no significant difference in the 5‐year overall survival (95% confidence interval (CI): −0.21–0.20, Z = 0.07, P = 0.94) for randomized control trials, (95% CI: −0.51–0.02, Z = 1.85, P = 0.07) for non‐randomized control trials and (95% CI: −0.26–0.06, Z = 1.20, P = 0.23) for all the studies. Conclusions Although ERP is a safe procedure, it did not offer a significant improvement in survival, while at the same time leading to an increased incidence of severe diarrhoea for at least 1 year, thus leaving the standard pancreaticoduodenectomy as the surgical method of choice for the treatment of pancreatic head adenocarcinoma.